Features of Antibiotic Therapy of Patient with Complicated Diabetic Foot Syndrome and Sepsis - Shapoval, S. D.; Savon, I. L.; Trybushnyi, O. V.; Slobodchenko, L. Yu.; Шаповал, Сергій Дмитрович; Савон, Ігор Леонідович; Трибушний, Олег Володимирович (My University, 2023)
Examined and treated 1246 patients with complicated diabetic foot syndrome (DFS) for the period from 2010 to 2015 (326 patients - a comparison group, 888- main groups - representative) and of 32 patients in the Development of Sepsis. Found that in patients with pyonecrotic processes of DFS in which surgery is performed in an ambulatory, ABT can be administered in the tablet forms. Patients of groups II-III the one should remember that in the presence of sensitivity to multiple antimicrobials, use sequence - from the weaker to the stronger, and at the risk of MRSA – linezolid, daptomycin. With the development of sepsis - drugs of choice are fluoroquinolones of III - IV generation, carbapenems, and the presence of MRSA – linezolid, daptomycin or vancomycin. Suggested tactics of ABT contributed to the reduction of length of hospitalization, with an average of (31,4±1,8) to (19,4±2,3) patient days (t=3,32; P<0,05), and the reduction of postoperative mortality from 7,5 to 3,8% (x2=6,74; P<0,05).
Keywords: diabetic foot syndrome; sepsis; antibiotic therapy